BIBLIOMETRIC ANALYSIS OF THEMES AND TRENDS IN ORGANOPHOSPHORUS POISONING RESEARCH WITH TEXT MINING. - Avinash J. Pujari; Bidhan Dolai (Student’s Journal of Health Research Africa, 2023)
Background: Organophosphorus poisoning is a global health concern.This study uses an integrated strategy to assess the research landscape, combining quantitative analysis of publishing trends with automated extraction of information from text data. Methodology: R-based biblioshiny is used for integrated text mining and bibliometrics on organophosphorus poisoning research. Search query is filtered from language, publication type, and date to ensure relevant and recent articles. RStudio and biblioshiny package is used for data retrieval and analysis. This research article thematic direction analyses associations between acetylcholinesterase and animals, insects, zebrafish, and humans in forensic medicine and toxicology covering the period from 2013 to 2022. Results: The data provided presents trends in organophosphorus poisoning research topics, including frequency, temporal distribution, and prominence. Notable trends include early focus on pralidoxime, atropine, and suicide attempts in 2014-2015, shifting towards pesticides, organophosphate poisoning, humans, and compounds in later years. Different age groups and retrospective studies are widely explored in research. Conclusion: The integrated strategy of text mining and bibliometrics employed in this study has provided a wealth of valuable insights into the research landscape of organophosphorus poisoning.